IL-12 and GM-CSF engineered dendritic cells enhance the enrichment and selection of tumor-reactive T cells for cancer immunotherapy - Liu, Zhen; Li, Haoyun; Gao, Zhaoya; Cheng, Ruoqi; Lu, Jiahua; Che, Xuan; Dong, Jiebin; Wang, Zilong; Cui, Zejia; Gu, Jin; Bai, Yun; Li, Cheng; et al. (Frontiers in Immunology, 2025)
The use of tumor-reactive T cells in targeted tumor elimination holds significant potential for cancer immunotherapy, such as Tumor-Infiltrating Lymphocyte (TIL) therapy and TCR-T adoptive immunotherapy. Critical aspects of the effective clinical application of these immunotherapies include the enrichment and selection of tumor antigens and their corresponding reactive T cells. However, current in vitro methods for expanding and screening tumor antigen-reactive T cells remain inefficient. One reason for this inefficiency is the dysfunctional state of tumor-reactive T cells, which limits their expansion and activation. To address this challenge, we developed an optimized dendritic cell-based culture system, in which dendritic cells simultaneously express interleukin-12 and granulocyte-macrophage colony-stimulating factor (12GM-DCs), to enhance the expansion of tumor-reactive T cells. We found that 12GM-DCs can enrich reactive T cells targeting various tumor antigens, including virus-associated tumor antigens, tumor-associated antigens, mutant tumor neoantigens, and patient-specific tumor neoantigens. Moreover, 12GM-DCs increased the proportion of antigen-specific T cells, enhanced the activation of those T cells, and promoted the maintenance of a memory phenotype. The cytotoxicity of these antigen-reactive T cells was increased after co-culture with 12GM-DCs, likely due to the increased secretion of interferon-γ and granzyme B. Importantly, these functions and phenotypic advantages of tumor antigen-reactive T cells derived from the 12GM-DC culture system could be effectively maintained and the antitumor activity was also enhanced in tumor-burden mice. Our 12GM-DC coculture system effectively enriches antigen-specific T cells and has the potential to advance the clinical application of cancer immunotherapy by targeting tumor antigens and their reactive T cells.